DIRECTIONS OF THE ORGANIZATIONAL AND INVESTMENT MECHANISM OF AGRICULTURAL LANDSCAPES USE - Oksana Ivanivna DREBOT; Mykola Kharitonovich SHERSHUN; Lyudmila Ivanivna SAKHARNATSKA; Mariya Yaroslavivna VYSOCHANSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the study was to carry out an economic analysis of strawberry production in the Aydın province of Turkey which has a significant potential for strawberry production. The main material of the study was comprised of data acquired via survey method from 59 greenhouse strawberry producers in the Sultanhisar and Köşk districts of the Aydın province. The producers were classified according to their size as Group I (1-10 decares; 17 farms), Group II (11-25 decares; 20 farms), Group III (26-50 decares; 14 farms) and Group IV (>50 decares; 8 farms). Average strawberry land presence in establishments was 27.19 da and the share of strawberry lands in total land presence was calculated as 52.64 %. The ratio of producers using certified seedling was observed to be highest in Group IV (100 %) and lowest in Group I (47.06 %). The strawberry varieties produced most frequently were determined as Rubygem, Fortuna and Festival. Establishment costs per decare according to the total producer average was calculated as 4955.07 TL. Seedling costs (42.86 %) were determined to have the highest share among the establishment costs. Production costs according to all farm groups average was determined as 3101.56 TL/da. It was determined that labor cost is ranked number one among the total production costs (29.91 %). It was determined that the gross, net and relative return per decare according to farm groups increases with increasing farm size. It was observed that larger farms are more advantageous with regard to economic criteria.